2013
DOI: 10.1007/s10658-013-0314-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and molecular mechanisms of resistance to powdery mildews in tomato (Solanum lycopersicum) and its wild relatives

Abstract: Powdery mildews (PMs) cause disease in a wide range of plant species including important crops. Taking tomato as an example, here we review findings on the genetic basis and mechanisms of plant resistance to PMs. First, we present a summary of our research on tomato resistance to two PM species, with the focus on Oidium neolycopersici. We discuss the genetics of resistance to this pathogen in tomato. Then, we compare different forms of resistance mediated by different resistance genes based on molecular and cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 151 publications
(225 reference statements)
0
33
0
Order By: Relevance
“…Research in the last 15 years has broadened knowledge of the genetic basis of resistance to O. neolycopersici (Lindhout et al 1994b;Ciccarese et al 1998;Huang et al 2000b;Bai et al 2003Bai et al , 2004Bai et al , 2005Li et al 2006Li et al , 2007Li et al , 2008Li et al , 2012Seifi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research in the last 15 years has broadened knowledge of the genetic basis of resistance to O. neolycopersici (Lindhout et al 1994b;Ciccarese et al 1998;Huang et al 2000b;Bai et al 2003Bai et al , 2004Bai et al , 2005Li et al 2006Li et al , 2007Li et al , 2008Li et al , 2012Seifi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Early after the appearance and rapid spread of the disease in Europe and North America (Kiss et al, 2005), breeding programs have been started because all the commercial tomato cultivars were susceptible to O. neolycopersici at that time (Lebeda et al, 2014;Seifi et al, 2014). Wild relatives of tomato were used as valuable sources of resistance (e.g., Lebeda et al, 2014) and the cytological and molecular background of powdery mildew resistance was also deciphered in Solanum spp.…”
Section: Introductionmentioning
confidence: 99%
“…Wild relatives of tomato were used as valuable sources of resistance (e.g., Lebeda et al, 2014) and the cytological and molecular background of powdery mildew resistance was also deciphered in Solanum spp. (e.g., Seifi et al, 2014). The biology, host range and sporulation mechanisms of the pathogen were studied in detail, as well (e.g., Mieslerová et al, 2004;Jankovics et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This carries a loss-of-function mutation in the tomato homolog SlMLO1 and is thus resistant to the fungus O. neolycopersici, causing PM in tomato Seifi et al 2014). We assumed that restoration of PM symptoms upon SmMLO1 overexpression would have proven functional conservation with the susceptibility gene SlMLO1.…”
Section: Eggplant Smmlo1 Complements Tomato Slmlo1 In a Functional Comentioning
confidence: 99%
“…It can be host of three PM species, namely Oidium neolycopersici, Oidium lycopersici and Leveillula taurica (Seifi et al, 2014). Since 1996, when it was found that all the tomato cultivars were susceptible to O. neolycopersici, extensive researches were conducted by our group for sources of resistance (Seifi et al, 2014). An allele containing a 19 bp deletion in the coding region of the PM susceptibility gene SlMLO1 was found in a wild accession of S. lycopersicum var.…”
Section: Introductionmentioning
confidence: 99%